Bounded probability based textual data compression for fiber-optic communication - Paul Alapatt, Bosco; Kavitha, A (International Journal of Engineering and Technology, 2019)
Fiber optic communication becomes very popular due to its nature of high data rate. Though fiber optic communication offers faster data transmission, it suffers from the drawback of massive amount of data being generated, stored or transmitted. Data compression techniques are introduced to minimize the size of data which eventually reduces the bandwidth utilization, storage space and data transmission at a faster rate. This paper presents a new dictionary based encoding technique called Bounded probability based textual data compression algorithm called BPT algorithm. The BPT algorithm generates a codeword based on the dictionary, which contains the binary code based on the probability of occurrence of characters in the input data. For decompression, there is a need to transmit the coding table along with the compressed data. The proposed BPT algorithm is tested using a set of benchmark textual dataset from The Calgary Corpus and The Canterbury Corpus. The experimental results verified the superiority of the BPT algorithm over the state of art methods in terms of different measures namely compression ratio (CR), compression factor (CF), bits per character (bpc) and space savings. Â Â